درجة توافر عناصر التمكين الإداري للقيادات النسائية في كلية التربية بجامعة الملك سعود - المطيري، نوف عبدالله ثواب; الجارودي، ماجدة بنت إبراهيم بن حسن (دار سمات للدراسات والأبحاث, 2016)
This study aimed to identify the degree of availability of the elements of the administrative empowerment of women leaders in the College of Education at King Saud University, and to achieve the objectives of the study the researcher has used the descriptive survey. The Questionnaire was also used as a tool to study the collection of data from fourteen women leaders at King Saud University. the study showed: the elements of the administrative empowerment among women leaders in the College of Education are available at King Saud University in a medium range , where work and training team comes in the first place among the elements of the administrative empowerment, followed by effective communication, and in the fourth place comes the delegation of authority, At last motivation considered as the least element in the administrative empowerment among women leaders in the College of Education at King Saud University. Furthermore the results showed that there were no statistically significant differences at the level of (0.05) or less between the averages of the study sample responses about the degree of availability of the elements of the administrative empowerment of women leaders in the College Education depending on the differences of years of experience and educational qualifications. As a result of the surveys and the studies the researcher has made several suggestions.
هدفت الدراسة الحالية إلى التعرف على درجة توافر عناصر التمكين الإداري للقيادات النسائية في كلية التربية بجامعة الملك سعود، ولتحقيق أهداف الدراسة استخدمت الباحثة المنهج الوصفي المسحي. كما استخدمت الاستبانة كأداة لجمع بيانات الدراسة من مجتمعها المتمثل في القيادات النسائية في كلية التربية بجامعة الملك سعود والبالغ عددهن (14) فردا. أشارت النتائج إلى توافر عناصر التمكين الإداري لدى القيادات النسائية في كلية التربية بجامعة الملك سعود بدرجة متوسطة، حيث بلغ المتوسط الحسابي العام (3.14) وقد جاء محور فريق العمل والتدريب بالمرتبة الأولى من بين عناصر التمكين الإداري، يليهما الاتصال الفعال، وبالمرتبة الرابعة يأتي تفويض السلطة، وفي الأخير يأتي التحفيز كأقل عناصر التمكين الإداري لدى القيادات النسائية في كلية التربية بجامعة الملك سعود. كما وأوضحت النتائج أنه لا توجد هناك فروق ذات دلالة إحصائية عند مستوى (0.05) فأقل بين متوسطات استجابات أفراد عينة الدراسة نحو درجة توافر عناصر التمكين الإداري للقيادات النسائية في كلية التربية باختلاف متغيري سنوات الخبرة والمؤهل العلمي، وفي ضوء النتائج التي تم التوصل لها قدمت الباحثة عدد من التوصيات والمقترحات.
Keywords: التمكين الإداري -- القيادات النسائية -- جامعة الملك سعود